Spatiotemporally-controlled transgene expression in hydroxyapatite-fibrin composite scaffolds using high intensity focused ultrasound. (February 2019) - Moncion, Alexander; Harmon, Jonah S.; Li, Yan; Natla, Sam; Farrell, Easton C.; Kripfgans, Oliver D.; Stegemann, Jan P.; Martín-Saavedra, Francisco M.; Vilaboa, Nuria; Franceschi, Renny T.; Fabiilli, Mario L.
Abstract: Conventional tissue engineering approaches rely on scaffold-based delivery of exogenous proteins, genes, and/or cells to stimulate regeneration via growth factor signaling. However, scaffold-based approaches do not allow active control of dose, timing, or spatial localization of a delivered growth factor once the scaffold is implanted, yet these are all crucial parameters in promoting tissue regeneration. To address this limitation, we developed a stable cell line containing a heat-activated and rapamycin-dependent gene expression system. In this study, we investigate how high intensity focused ultrasound (HIFU) can spatiotemporally control firefly luciferase (fLuc) transgene activity both in vitro and in vivo by the tightly controlled generation of hyperthermia. Cells were incorporated into composite scaffolds containing fibrin and hydroxyapatite particles, which yielded significant increases in acoustic attenuation and heating in response to HIFU compared to fibrin alone. Using 2.5 MHz HIFU, transgene activation was observed at acoustic intensities of 201 W/cm 2 and higher. Transgene activation was spatially patterned in the scaffolds by rastering HIFU at speeds up to 0.15 mm/s. In an in vivo study, a 67-fold increase in fLuc activity was observed in scaffolds exposed to HIFU and rapamycin versus rapamycin only at 2 days post implantation. Repeated activation of transgene expression was also demonstrated 8 days after implantation. No differences in in vivo scaffold degradation or compaction were observed between +HIFU and -HIFU groups. These results highlight the potential utility of using this heat-activated and rapamycin-dependent gene expression system in combination with HIFU for the controlled stimulation of tissue regeneration. Graphical abstract: